2023
DOI: 10.1186/s12884-023-05605-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy BMI, MTHFR polymorphisms, and the risk of adverse pregnancy outcomes in pregnant women from South China: a retrospective cohort study

Abstract: Background Increasing evidence suggests an association between maternal pre-pregnancy body mass index (pre-BMI) and adverse pregnancy outcomes. However, the effects of methylenetetrahydrofolate reductase (MTHFR) polymorphisms on these relationships require further investigation. This study aimed to investigate whether the relationship between pre-BMI and the risk of adverse pregnancy outcomes was influenced by MTHFR gene polymorphisms. Methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…( 37 ) and Wang et al. ( 35 ) showed an impact on the overall results in the allele model ( Supplementary Figure 1A ), and several studies ( 14 , 28 – 30 , 32 , 37 , 39 , 40 31 , 35 , 38 ) showed an impact on the overall results in the heterozygote model ( Supplementary Figure 1C ). Thus, more high-quality studies are still needed to further confirm our findings.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…( 37 ) and Wang et al. ( 35 ) showed an impact on the overall results in the allele model ( Supplementary Figure 1A ), and several studies ( 14 , 28 – 30 , 32 , 37 , 39 , 40 31 , 35 , 38 ) showed an impact on the overall results in the heterozygote model ( Supplementary Figure 1C ). Thus, more high-quality studies are still needed to further confirm our findings.…”
Section: Resultsmentioning
confidence: 84%
“…Initially, 112 records were identified from the six databases. Ultimately, a total of 18 available studies were included in this meta-analysis after reviewing the titles, abstracts and full texts (14,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…Insufficient maternal intake can lead to malnutrition, and lower weight gain is associated with an increased risk of adverse maternal and infant outcomes. 35,36 Rudra et al 37 have identified a lower BMI in pregnant women as a risk factor for PROM and an increased risk of HCA. Consistent with these findings, our study also showed a lower BMI in the HCA group, and it acted as a protective factor in the combined model, indicating that appropriate weight gain before delivery was associated with a lower incidence of HCA.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similarly, our previous studies had indicated that pregnant women who were obese, with the CT þ TT genotype, were 2.40 times more likely to have GDM, whereas no significant association was observed in those with the CC genotype. 31 In addition, an…”
Section: Discussionmentioning
confidence: 99%